Determination of the Safe Surgical Margin for T1b Renal Cell Carcinoma - Zhang, Kan; Xie, Wen Lian (Urology Journal, 2017)
Purpose: To determine the rational surgical margin for pathological T1b renal cell carcinoma (RCC). Materials and Methods: This retrospective study included surveys of 60 patients with T1bN0M0 RCC who underwentradical nephrectomy (RN, n = 40) or partial nephrectomy (PN, n = 20) between October 2008 and December2014 at the Sun Yat-sen Memorial Hospital affiliated with Zhongshan University. Specimens were collectedfrom 6 sites at the tumour periphery for RN and PN, and at suspected sites on the tumour surface for PN in addition.The histological subtype, pathological grade, surgical margin, pseudocapsule completeness, distribution of satellitefoci, and largest distance between the extra-pseudocapsule lesion and primary tumour (DEP) were evaluated. Thispaper will analyse the relationships between these factors. Results: The positive surgical margin rate was 10% in patients undergoing PN. The study found no significantrelationships between the incidence of satellite foci and tumour diameter, Fuhrman grade, or histological subtype(all P > 0.05). However, male sex, positive surgical margins, and an incomplete pseudocapsule were associatedwith the incidence of satellite foci (P < 0.05). Cases with satellite foci tended to show positive surgical margins.The DEP was <1.0 mm for all tumours, but there were no significant relationships between the DEP and the tumourdiameter, pathological grade, or histological subtype (P > 0.05). Conclusion: In T1b RCC, a 1-mm surgical margin would be sufficient to attain integrated resection of the primarytumour and its cancerous tissue beyond the pseudocapsule. PN was insufficient to prevent a positive surgical margin,most likely due to the presence of satellite foci.